(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The importance of this study lies in its exploration of proposed planning strategies to address the phenomenon of urban encroachment in Najaf Governorate. It highlights the social and economic characteristics of residents in informal settlements, emphasizing their dangers and the implications for human life. A thorough understanding of the environment in these areas enables officials, engineers, and planners to develop effective programs for improvement and significantly mitigate associated risks. The study also examines the reality of informal settlements and their negative impacts while identifying key urban characteristics of these residential areas. Thus, the study aims to explore planning approaches derived from global experiences to eliminate or reduce the spread of informal settlements and prevent their future emergence. The study found that the number of families in Najaf in 2019 was 218,903, while the number of housing units in the governorate that same year was 208,498. This indicates a housing deficit of 10,405 units, in addition to the number of units occupied by squatters, estimated at 53,810, and the dilapidated units, totalling around 5,212. This means the governorate needs 69,427 housing units to achieve adequate housing. The study also revealed a variation in the number of informal housing clusters, which numbered 27 in 2014 and increased to 89 by 2017, with the district of Kufa ranking first with 18 informal clusters.